Behaviour of Using Personal Protective Equipment by Midwives During Normal Childbirth Based on Health Belief Model and Social Capital at Maternity Clinics - Azarine Dwinta Framudella; Nurfika Asmaningrum; Leersia Yusi Ratnawati (Indonesian Journal of Global Health Research, 2025)
The implementation mechanism of normal childbirth care is inseparable from the potential risks to midwifery health disorders. One of the efforts to prevent health problems due to work is to use Personal Protective Equipment (PPE). The behavior of using PPE by midwives is important to prevent work accidents or occupational diseases during normal childbirth assistance which can be reviewed from a person's health behavior. Theories that can describe health behaviors are the Health Belief Model and Social Capital. The purpose of this study is to analyze the influence of the theory of Health Belief Model and Social Capital on the behavior of using PPE in midwives in normal childbirth care at the Surabaya City maternity clinic. The research design uses clinical observation with a cross sectional approach. The population consists of 80 midwives and the sample consisted of 66 respondents. All aspects of HBM and social capital have a sig > 0.05 which means that these aspects are related to the behavior of using PPE in midwives in normal childbirth care at the Surabaya City maternity clinic. All aspects of HBM and social capital have a sig of < 0.05 which means that these aspects affect the behavior of using PPE in midwives in normal childbirth care at the Surabaya City maternity clinic. The vulnerability aspect of HBM theory and the proactive action aspect of Social Capital theory significantly affect normal childbirth care.